Wealth in the Perspectives of the Quran - Suhaimi, Suhaimi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Wealth is a matter of great urgency in human life, and it is not surprising that everyone needs it. Many people are even preoccupied with accumulating wealth without caring whether it is rightfully obtained or not. The Quran itself, as the guidance for Muslims, extensively discusses the concept of wealth. Therefore, this article aims to uncover the Quran's perspective on the essence of wealth, its acquisition, and its utilization by examining and analyzing the writings of Quranic scholars through a qualitative descriptive approach. The expected outcome is to enhance our comprehensive understanding of wealth and enable us to implement it correctly and responsibly in real life. In general, wealth in the Quranic view is inherently linked to two aspects: a gift and trust from Allah that should be appreciated, and a trial that must be approached with caution. This is because wealth not only has the potential to positively impact the owner's future (afterlife), but can also have negative consequences. Hence, it requires high knowledge and awareness regarding its acquisition and utilization.